A numerical modelling criterion for the analysis of underground openings using infinite elements - Kumar, Prabhat (Applied mathematical modelling, 1986)
Underground openings subject to and initial stress field are usually analysed by the finite element method (FEM) by truncating the analysis domain at a large but finite distance from the zone of disturbance. In this paper, the problem is analysed by the method of finite (FE) and infinite elements (IE)to represent near- and far-fields, respectively. Deep openings of circular and elliptical shape and shallow circular openings are analysed to establish the approach. The numerical results of stress concentration factors are compared with analytical results and a satisfactory agreement is found. The mesh configurations and the finite/infinite element (FIE) interface locations are systematically varied to establish a numerical modelling criterion for the most effective use of this approach. It is asserted that the truncation approach may now by abandoned in view of the proposed approach, its applicability and advantages.